Interest Rate in the Relationship Between Fundamental Factors and Efficiency of Indonesian Regional Development Banks (2020–2024) - Sora Baltasar; Sri Retnaning Sampurnaningsih; Sahroni Sahroni; Rachmawaty Rachmawaty; Zulfitra Zulfitra (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the effects of key financial ratios, namely Capital Adequacy Ratio, Return on Assets, and Non-Performing Loans, along with the moderating role of interest rates on the operational efficiency of Regional Development Banks in Indonesia, measured by the Cost-to-Income Ratio (CIR). A quantitative approach is employed using panel data from 2020–2024, with model selection indicating the Random Effects Model as the most appropriate specification, complemented by Moderated Regression Analysis to capture interaction effects. The results show that Return on Assets has a negative and significant effect on CIR, confirming that profitability plays a central role in enhancing efficiency. In contrast, Capital Adequacy Ratio and Non-Performing Loans do not exhibit strong partial effects, although interest rates significantly moderate their relationships with efficiency. Simultaneous testing confirms that internal financial factors jointly influence operational efficiency. These findings suggest that efficiency is shaped not only by internal performance but also by its interaction with monetary conditions. The study provides implications for improving capital allocation, profitability management, and adaptive risk strategies to sustain efficiency.